Human Heart Rate Detection With Web Monitoring: - Ritzkal Ritzkal; Bayu Adhi Prakosa2; Rendi Juhar Maulana (Jurnal Mantik, 2021)
Monitoring heart rate and body temperature is one of the tools to find out information on body health, especially heart conditions and body temperature. There are still some health places that still use the manual method of monitoring heart rate and body temperature, especially general practitioners' practices. By using the Hardware Pulse sensor and the Ds18b20 as a microcontroller, it is easier for us to find out information about heart rate and body temperature that can be viewed digitally. This monitoring makes it easier for doctors to get information about heart rate and body temperature as a follow-up material for doctor's examinations which can be viewed via the LCD on the device and the WEB with the help of Ethernet Shield as a system tool to connect to the internet network. With a heart rate and body temperature monitoring device, you can find out the condition of your heart and body temperature "Low, Normal, and High". By utilizing the Arduino Uno microcontroller as the main electronic data receiver to process data previously data through the Pulse sensor as input for heart rate data and the Ds18b20 as input for body temperature data which will then be displayed on the LCD and WEB, in order to make it easier to get information on the patient's heart rate and body temperature. efficiently and effectively.